2017
DOI: 10.1136/medethics-2015-103365
|View full text |Cite
|
Sign up to set email alerts
|

Neutralising fair credit: factors that influence unethical authorship practices

Abstract: This study experimentally tests whether the techniques of neutralisation as identified in the criminal justice literature influence graduate student willingness to engage in questionable research practices (QRPs). Our results indicate that US-born graduate students are more willing to add an undeserved coauthor if the person who requests it is a faculty member in the student's department as opposed to a fellow student. Students are most likely to add an undeserving author if a faculty member is also their advi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…[34][35][36] While our methods captured some of the messiness of authorship practices, these narratives did not reflect the conflicted nature of authorship that the literature on responsible conduct of research might suggest. 2,[9][10][11][12][13][14][15][17][18][19][20][21] Participants did not narrate overt conflict related to these 24 papers (only three narratives were contested, and these contested elements were subtle) and frequently stressed the helpful actions and resources of team members. Rather than reflecting the improvisational negotiation of conflicting norms, 22 these narratives suggested that authorship is an agreeable space of productive work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] While our methods captured some of the messiness of authorship practices, these narratives did not reflect the conflicted nature of authorship that the literature on responsible conduct of research might suggest. 2,[9][10][11][12][13][14][15][17][18][19][20][21] Participants did not narrate overt conflict related to these 24 papers (only three narratives were contested, and these contested elements were subtle) and frequently stressed the helpful actions and resources of team members. Rather than reflecting the improvisational negotiation of conflicting norms, 22 these narratives suggested that authorship is an agreeable space of productive work.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] These studies have also identified factors beyond ICMJE criteria that may influence authorship, including: reciprocity (e.g., to return a favor to someone who helped in some way in the past); feelings of loyalty or obligation, particularly to advisors or mentors; beliefs that the existing criteria do not take into account the important "minutiae of research beyond writing and data reduction"; 15 and institutional and social structures and hierarchies like tenure status, gender, and minority status. 2,11,15,[17][18][19][20][21] Despite guiding criteria, then, the social practice of authorship remains a contested one in that published criteria and enacted practice do not always align.…”
Section: I We and They: A Linguistic And Narrative Exploration Of The Authorship Processmentioning
confidence: 99%
“…This inadequacy suggests that there are further RCR-related issues among faculty and other university research stakeholders worth exploring. For example, Trinkle et al (2017) found that faculty were able to pressure students into questionable research practices, like egregious honorary authorship, despite their receiving prior RCR training. This finding suggests that variables, beyond receipt of RCR training, influence the culture of RCR adherence on university campuses.…”
Section: Need and Gap For Studymentioning
confidence: 99%
“…The authorship form can also help lessen unfair authorship practices that result from power imbalances. For example, Trinkle et al (2017) found that students were more likely to add faculty members as undeserving authors, especially if the faculty member was also their advisor. While our method does not provide a full solution for this problem, we still hope that an emphasis on transparency and clarity on contributions can partially neutralize some of these power imbalances.…”
Section: Solving Common Authorship Problemsmentioning
confidence: 99%